Basic Quantitative Research Methods for Urban Planners, 1st edition Reid Ewing, Keunhyun Park - Ewing, Reid (Routledge, 2020)
In most planning practice and research, planners work with quantitative data. By summarizing, analyzing, and presenting data, planners create stories and narratives that explain various planning issues. Particularly, in the era of big data and data mining, there is a stronger demand in planning practice and research to increase capacity for data-driven storytelling.